Problems of the Legal Regulation and Practice of Enforcing Additional Punishment for Corruption-Related Offenses in Kazakhstan - KASSENOVA, Ainur Mahmutovna (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
The article considers theoretical and applied issues of the legal regulation of enforcing additional punishment for corruption-related offenses in Kazakhstan. Corruption in Kazakhstan has got widespread in society and government bodies. Nowadays, it is a threat to national security and causes significant damage to the social and economic development of the country. Reasons for the current situation in the sphere of anti-corruption measures include the insufficient scientific study of the problem, poor understanding of the nature and features of additional punishment, defects in the prescription of additional punishment, as well as objective and subjective obstacles to its enforcement.